The suspension of the free movement of foreign direct investment in Spain due to the Covid-19 crisis - Esplugues Mota, Carlos (CUADERNOS DE DERECHO TRANSNACIONAL, 2020)
The free movement of investment is one of the mantras that has characterized economic modernity. Nevertheless, the principle is under increasing criticism in the framework of a world under a geostrategic readjustment. States are interested in preventing certain strategic assets and critical infrastructures to be controlled by foreign investors, in many cases, owned or controlled by foreign States. And this goal fosters the designation of national screening systems of evaluation of foreign investment on national security grounds. Unlike other western countries, Spain had been so far reluctant to this trend, but things have now changed deeply because of the COVID-19 crisis.
Keywords: foreign investment; free circulation of foreign investment; screening of foreign investment; national security; COVID-19